Malay Version of Moral Identity Scale: A Cross-Cultural Validation In Malaysian Youth - Yusoff, Nasir; Shaharum, Muaz Haqim; Kueh, Yee Cheng (IIUM Medical Journal Malaysia, 2022)
Introduction: The Moral Identity Scale (MIS) measures the construct of moral identity – internalization and symbolization. This study aims to translate and validate the original English version of MIS to the Malay language version. Methods: The 10 items of MIS (five items of symbolization and five items of internalization) were translated to the Malay language through forward and backward procedures. A total of 388 youth-aged participants were involved in this online survey. Participants’ age ranged from 18-24 years old. More than half were females. Results: The construct of moral identity was maintained with the re-modeling of internalization. The final model suggested retaining the three internalization items and five symbolization items. Discriminant validity and the construct reliability of the two factors were satisfactory (symbolization=0.81, internalization=0.69). Internal consistencies indicated acceptable Cronbach’s alpha values for both symbolization (0.85) and internalization (0.81). Test-retest Intraclass Correlation Coefficient (ICC) was good and satisfactory (internalization=0.79 and symbolization=0.81). Conclusion: The Malay version of MIS is a reliable tool and free from cultural bias which is useful to be applied in a public health-related program.